2002
DOI: 10.1046/j.1529-8817.2002.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

RESPONSE TO SALINITY AND HEAT STRESS IN TWO HALOTOLERANT CHLOROPHYTE ALGAE1

Abstract: Two new isolates of halotolerant chlorophyte algae from the Salt Plains National Wildlife Refuge in Oklahoma, USA, tentatively identified as Dunaliella sp. Teodoresco and Nannochloris sp. Naumann, were characterized with respect to interaction between growth salinity and short-term heat tolerance. Cells were cultured at 23-25 Њ C over a wide range of salinity. In both species, salinity alone had little effect on maximum photochemical yield (measured by pulse modulated fluorescence) and integrity of the light h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 38 publications
4
28
0
Order By: Relevance
“…Six individuals from each of the seven populations were measured after being cultured for 72 h at different temperatures. Optimal chlorophyll fluorescence quantum yield was calculated according to the following equation: (Parkhill et al 2001;Henley et al 2002). F o and F m refer to the minimum fluorescence and the maximum fluorescence from dark adapted samples, respectively.…”
Section: Measurements Of Photosynthetic Activitymentioning
confidence: 99%
“…Six individuals from each of the seven populations were measured after being cultured for 72 h at different temperatures. Optimal chlorophyll fluorescence quantum yield was calculated according to the following equation: (Parkhill et al 2001;Henley et al 2002). F o and F m refer to the minimum fluorescence and the maximum fluorescence from dark adapted samples, respectively.…”
Section: Measurements Of Photosynthetic Activitymentioning
confidence: 99%
“…Environmental factors have been reported to influence the chemical composition of microalgae. For instance, the effect of light, nutrients, temperature, pH and salinity has been well documented (Richmond 1986;Henley et al, 2002). In addition, the growth phase has been reported as an intrinsic factor influencing the growth rate and biochemical composition of microalgae (Renaud et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that salinity stress predisposes photosystem II (PSII) to photoinhibitory damage (Lu et al 2002;Maricle et al 2007;Hichem et al 2009;Qin et al 2010Qin et al , 2011Sui et al 2010). However, very little attention has been paid to the responses of PSII to salinity stress and high-temperature stress in combination (Henley et al 2002). It is obviously important from an ecophysiological viewpoint to study the combination of these two stresses, given that about one-third of the irrigated land worldwide is already experiencing increased salinity (Epstein et al 1980; Photosynthesis of mulberry at stress conditions 405 Epstein 1984).…”
Section: Introductionmentioning
confidence: 99%